Safety and efficacy of a feed additive consisting of an essential oil from the herbaceous parts of Pelargonium graveolens L‘Hér. (geranium rose oil) for all animal species (FEFANA asbl) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Mojca Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; Alena Pechová; et al. (EFSA Journal)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of an essential oil obtained from the herbaceous parts of Pelargonium graveolens L‘Hér. (geranium rose oil), when used as a sensory additive in feed and water for drinking for all animal species. The EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) concluded that the use of geranium rose oil is safe up to the maximum proposed use levels of 5 mg/kg complete feed for all animal species. The FEEDAP Panel considered that the use in water for drinking is safe provided that the total daily intake of the additive does not exceed the daily amount that is considered safe when consumed via feed. No concerns for consumers were identified following the use of geranium rose oil up to the maximum proposed use level in feed. The additive under assessment should be considered as irritant to skin and eyes, and as a skin and respiratory sensitiser. The use of geranium rose oil at the proposed use level in feed was not expected to pose a risk to the environment. Since P. graveolens and its preparations were recognised to flavour food and its function in feed would be essentially the same as that in food, no further demonstration of efficacy was considered necessary.